Management of a Complicated Crown Fracture in a Tertiary Care Hospital (Journal of Enam Medical College, 2017)
Restoration of a fractured tooth is routinely performed in clinical practice. Many factors are considered in an effort to provide optimal mechanical properties, aesthetics, longevity as well as patient acceptance. In this type of challenging endeavour, main effort should be made to save as much of the coronal tooth structure to increase survival rate of endodontically-treated teeth. This case report presents a 35-year-old male with an oblique complicated crown fracture of maxillary left central incisor tooth. The procedure used to repair the fracture was gingivectomy followed by endodontic treatment. The root canal was filled with a root canal sealer and gutta-percha points. After root canal obturation, the tooth was restored with a glass fiber post and composite resin without additional crown coverage. The restoration made it possible to maintain the remaining tooth structure in a good occlusion and resulted in a high level of patient satisfaction.J Enam Med Col 2017; 7(1): 35-38